Fabrication of normally-off AlGaN/GaN metal–insulator–semiconductor high-electron-mobility transistors by photo-electrochemical gate recess etching in ionic liquid. (25th July 2016) - Zhang, Zhili; Qin, Shuangjiao; Fu, Kai; Yu, Guohao; Li, Weiyi; Zhang, Xiaodong; Sun, Shichuang; Song, Liang; Li, Shuiming; Hao, Ronghui; Fan, Yaming; Sun, Qian; et al.
Abstract: We characterized an ionic liquid (1-butyl-3-methylimidazolium nitrate, C8 H15 N3 O3 ) as a photo-electrochemical etchant for fabricating normally-off AlGaN/GaN metal–insulator–semiconductor high-electron-mobility transistors (MIS-HEMTs). Using the ionic liquid, we achieved an etching rate of ∼2.9 nm/min, which is sufficiently low to facilitate good etching control. The normally-off AlGaN/GaN MIS-HEMT was fabricated with an etching time of 6 min, with the 20 nm low-pressure chemical vapor deposition (LPCVD) silicon nitride (Si3 N4 ) gate dielectric exhibiting a threshold voltage shift from −10 to 1.2 V, a maximum drain current of more than 426 mA/mm, and a breakdown voltage of 582 V.